Performance of complete blood count (CBC) upon use of different anticoagulants in rats - Ali, Md Mottaleb; Azad, Nilima Rubaba; Haque, Md Iqramul; Sujan, Khaled Mahmud; Islam, Kazi Rafiqul; Islam, Md Kamrul (Asian Journal of Medical and Biological Research, 2020)
Complete blood count (CBC) is used as an index of health status of human and different animals as well as to diagnose a variety of diseases. Therefore, there is a growing need of using the most suitable anticoagulant to obtain the most appropriate hemogram. The present study was designed to assess the effect of different anticoagulants viz. Heparin, Sodium Citrate and EDTA on complete blood count (CBC) in rat with a view to choosing the best suitable candidate among the common anticoagulants. A total of 30 samples out of which 10 were for each type anticoagulant were collected from 10 apparently healthy rats of Long Evans strain. From each rat 6 ml of blood was drawn and subsequently divided into three different test tubes with three different anticoagulants. The samples were analyzed for their complete blood count (TEC, TLC, Hb, Hct, DLC, absolute leukocyte count, Red Cell Indices, RDW-SD, RDWCV, Platelet, MPV, PCT and PDW) using Sysmex XT-1800i Auto hematological analyzer. Results showed a significant (p<0.05) decrease in TLC, absolute neutrophil, and platelet count, and a significant (p<0.05) higher level of relative lymphocyte count in Sodium Citrate treated sample than with Heparin and EDTA. No significant changes were observed for RBC or erythrocyte indices among the three different groups. It can be concluded that samples treated with Sodium Citrate results in significant change in blood parameters. Therefore, it is better to use Heparin and EDTA than Sodium Citrate for complete blood count (CBC). Asian J. Med. Biol. Res. March 2020, 6(1): 16-21